Finite element simulation of high-speed cutting of nickel-based alloy - Yang Yong; Guo Yuwen; Wang Fengyu (MATEC Web of Conferences, 2016)
By analyzing microstructure of the material, a finite element model of high-speed cutting process more close to the practical instance was put forward. The microstructure of nickel-based alloy was obtained based SEM experiment, and the digital model of microstructure was built. Based on above study, finite element model of high-speed cutting of nickel-based alloy integrating macro and micro physical characters was established. Further, finite element simulation and analysis of high-speed cutting of nickel-based alloy were conducted, and the saw-tooth chip, cutting force variation curve and cutting temperature field distribution pictures were got. Research shows that grain boundary occur serious distortion at chip and tool contact area during saw-tooth chip forming, and the grain boundary structure changes will cause the change of cutting force during generating adiabatic shear band. So reducing cutting force and improving the processing quality can be achieved by changing the internal microscopic structure of workpiece.